Evaluation of human life at the time of the pandemic coronavirus - Đukić, Simo; Stančić, Sonja; Vuković, Mirna; Dimitrijević, Strahinja (Psihološka istraživanja, 2022)
The aim of this study was to determine whether people are subject to psychophysical numbness during the coronary virus pandemic and whether they estimate human lives to be less valuable as the numbers of those infected and who die from this virus increase. In two experiments, the contextual influence of the ratio of the number of cured-infected and positive-negative framework on the evaluation of the contribution of medical workers, as a measure of the value of human lives, respectively, was examined. In the third experiment, it was examined whether the type of inevitable disaster and the amount of money for repairing the consequences affect the evaluation of life. The contribution of medical workers in the first experiment was estimated by 354, 725, 729 respondents, respectively. The results suggest the assessment of the contribution of health workers does not depend on the number and percentage of curing, and the main effects of the scenario (pandemic curve) and framework (positive/negative) are not significant, while their interaction is statistically significant. The results of the third experiment suggest that the evaluation of human lives does not depend on the type of catastrophe (pandemic vs. flood) but that it depends on the amount of funds allocated for rescuing endangered people. These results have implications for decision-makers during disasters, who should avoid giving only numbers when reporting, but combine information on the number of survivors and deaths depending on the current situation, as well as report on individual cases, regardless of the type of disaster.